Histopatologi Organ Hepar Tikus Putih (Rattus norvegicus) setelah Paparan Asap Rokok Putih - Astrid Laksmita Djati; Sunarno Sunarno; Sri Isdadiyanto (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Cigarettes are tobacco products intended to be burned and inhaled, including white cigarettes, which use natural tobacco without additional ingredients, resulting in lower nicotine and tar levels. However, excessive smoking still poses a risk of organ damage, particularly to the liver, due to the presence of toxic chemical compounds in tobacco smoke. This study aimed to analyze the effects of white cigarette smoke exposure on the liver histopathology of white rats (Rattus norvegicus). A completely randomized design was used with 24 male rats (±200 g) divided into four groups: control (P0), exposure to one cigarette/day (P1), two cigarettes/day (P2), and three cigarettes/day (P3), each with six replications. The observed parameters included liver weight, hepatosomatic index, and the diameters of hepatic lobules, central veins, and hepatocytes. Data were analyzed using ANOVA followed by Duncan’s test at a 5% significance level. The results showed that exposure to white cigarette smoke had a negative effect on the diameter of the hepatic lobules, but did not have a negative effect on the other parameters. This study contributes to scientific understanding of the hepatotoxic effects of white cigarette smoke and provides a foundation for further research on the molecular mechanisms of liver injury caused by toxic compounds in tobacco smoke.